2022
DOI: 10.3390/jcm11195866
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Device-Based Cardiac Contractility Modulation Therapy on Left Ventricle Global Longitudinal Strain and Myocardial Mechano-Energetic Efficiency in Patients with Heart Failure with Reduced Ejection Fraction

Abstract: Background: Virtually all patients with heart failure with reduced ejection fraction have a reduction of myocardial mechano-energetic efficiency (MEE). Cardiac contractility modulation (CCM) is a novel therapy for the treatment of patients with HFrEF, in whom it improves the quality of life and functional capacity, reduces hospitalizations, and induces biventricular reverse remodeling. However, the effects of CCM on MEE and global longitudinal strain (GLS) are still unknown; therefore, this study aims to evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 36 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…A study also found up to a 70% reduction in the composite of cardiovascular death and HF hospitalization in appropriately selected patients [3]. In another study, CCM was associated with objective improvements in global longitudinal strain and myocardial mechano-energetic efficiency [4] In addition to increased cardiac contractility, CCM has been shown to contribute to improvement in calcium handling and reverse cardiac remodeling [5]. A recent multi-center pilot study suggests that these benefits may extend to patients with heart failure with preserved ejection fraction (HFpEF) [6].…”
mentioning
confidence: 91%
“…A study also found up to a 70% reduction in the composite of cardiovascular death and HF hospitalization in appropriately selected patients [3]. In another study, CCM was associated with objective improvements in global longitudinal strain and myocardial mechano-energetic efficiency [4] In addition to increased cardiac contractility, CCM has been shown to contribute to improvement in calcium handling and reverse cardiac remodeling [5]. A recent multi-center pilot study suggests that these benefits may extend to patients with heart failure with preserved ejection fraction (HFpEF) [6].…”
mentioning
confidence: 91%